Şefik Hüsnü Değmer'den İşçi Partisi'ne Aydınlık Hareketi'nin tarihsel süreci - Öcal, Enver Emre (My University, 2017)
Türkiye’nin ilk komünistlerinden olan Şefik Hüsnü Değmer’in öncülüğünde ortaya çıkan ve Türk siyasal hayatının tanıdık simalarından Doğu Perinçek’in liderliği ile varlığını devam ettiren, neredeyse bir asırlık bir politik hareket olan Aydınlık Hareketi’nin, varlığını muhafaza ettiği bu uzun yıllar içinde, geçirmiş olduğu teorik ve pratik evreler, politik dönüşümler, değişimler ve yaşadığı siyasal iniş ve çıkışlar nesnel şekilde incelenmeye çalışılmıştır.

This study tries to review objectively the theoretical and practical phases, political transformations, changes, and political ups and downs experienced by the Aydinlik Movement, an almost century-old political movement that was born under the leadership of Şefik Hüsnü Değmer, one of the first communists of Turkey, and carries on today under the leadership of Doğu Perinçek, one of the familiar faces in Turkish political life, throughout all those long years of survival. Since the subject of this review covers a large part of history, it was not possible to reflect the entire practical and theoretical accumulation put by the movement into practice.
Keywords: 2000’e Doğru Dergisi; Aydınlık; Aydınlık Dergisi; Aydınlık Gazetesi; Aydınlık Hareketi; Bora Dergisi; Communist Party of Turkey; Dogu Perincek; Doğu Perinçek; Enlightenment; Enlightenment Movement; İşçi Partisi Sefik Husnu; Kurtuluş Dergisi; Magazine Bora; Magazine Dawn; Magazine Enlightenment; Magazine Independence; Magazine Theory; Magazine Towards 2000; Proletarian Revolutionist Enlightenment; Proleter Devrimci Aydınlık; Revolutionist Workers’ Peasants’ Party of Turkey; Siyasi yönler; Socialist Party; Socialist Workers’ Peasants’ Party of Turkey; Sosyalist Parti; Sosyalizm; Şafak Dergisi; Şefik Hüsnü; Tarih; Teori Dergisi; Toplumsal hareketler; Turkish Socialism; Turkish Spartacists; Türk Sosyalizmi; Türk Spartakistleri; Türkiye; Türkiye İhtilalci İşçi Köylü Partisi; Türkiye İşçi Köylü Partisi; Türkiye İşçi ve Çiftçi Sosyalist Fırkası; Türkiye Komünist Partisi; Türkiye Sosyalist Emekçi Köylü Partisi; Workers Party; Workers’ and Farmers’ Socialist Party of Turkey; Workers’ Peasants’ Party of Turkey